2013
DOI: 10.1088/0004-637x/768/2/194
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: Star Clusters and the Neutral Hydrogen Medium of Tidal Tails

Abstract: Using archival data from ATCA, WSRT, and the VLA, we have analyzed the Hi emission of 22 tidal tail regions of the Mullan et al. sample of pairwise interacting galaxies. We have measured the column densities, line-of-sight velocity dispersions, and kinetic energy densities on ∼kpc scales. We also constructed a tracer of the line-of-sight velocity gradient over ∼10 kpc scales. We compared the distributions of these properties between regions that do and do not contain massive star cluster candidates (M V < -8.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 112 publications
4
14
0
Order By: Relevance
“…The surface density threshold for star formation is given by Schaye (2004) in terms of H i column density: N H,crit ∼ (3−10)×10 20 cm −2 . This value is in agreement with the column density required to detect clustered star formation as given by Mullan et al (2013).…”
Section: An Extremely High H I Mass To Stellar Light Ratiosupporting
confidence: 90%
“…The surface density threshold for star formation is given by Schaye (2004) in terms of H i column density: N H,crit ∼ (3−10)×10 20 cm −2 . This value is in agreement with the column density required to detect clustered star formation as given by Mullan et al (2013).…”
Section: An Extremely High H I Mass To Stellar Light Ratiosupporting
confidence: 90%
“…WALLABY will cover 75 percent of the sky (declination range of −90 • < δ < +30 • ) and is predicted to detect Hi in more than 500,000 galaxies out to a redshift of 0.26 with an angular resolution of 30 arcsec and a spectral resolution of 4 km s −1 (Duffy et al 2012, Koribalski 2012. This level of resolution is required to resolve the physical characteristics and measure the dynamical properties of tidally formed features in the nearby universe (Mullan et al 2013, Lelli et al 2015.…”
mentioning
confidence: 99%
“…This suggests that there may be small star formation events periodically in both tails, but the evidence of these events will rapidly fade away. Mullan et al (2013) found that tidal tails with large Hi line of sight velocity dispersion σ los and high Hi column densities were ideal locations for SCCs. Both the 3256 tails fit these criteron, and the majority of their SCCs, as determined by Knierman et al (2003) using HST WFPC2 data, lie in Hi pixels with these characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Tidal tails are signatures of galactic mergers (Schweizer 1978), illuminated by the ignition of star for-E-mail: mrodruck@psu.edu mation (Schombert et al 1990). Turbulent energy injected into the local Hi through these mergers compresses the gas, forming new stars (Renaud et al 2014); This is observationally shown in Mullan et al (2013), who were able to link the presence of Star Clusters Candidates (SCCs) to turbulent regions of Hi. While the young, in-situ formed SCCs of tidal tails have been studied in the past through imaging and spectroscopy (e.g.…”
Section: Introductionmentioning
confidence: 97%